Twins a practical guide to parenting multiples from conception to preschool - Bowman, Katrina; Ryan, Louise 1962- (Allen & Unwin, 2005)
This user-friendly guide explains how to prepare—emotionally and physically—for having and parenting more than one child. Based on extensive research as well as various parents' experiences of twin pregnancies, births, and toddlers, it offers sound advice from both medical and practical points of view. Detailed information and clear explanations of medical jargon are peppered with amusing and moving stories of catastrophe, chaos, and coping. From getting organized to breast feeding, and from finding time to sleep to toddler-proofing cupboards, this handbook offers useful advice for the new parents of twins or triplets.